THE IMPACT OF FAST-TRACK PROTOCOLS ON FUNCTIONAL RECOVERY AND QUALITY OF LIFE IN ONCOGYNECOLOGY - B. S. Muminov (Modern American Journals, 2026)
This study evaluates the effectiveness of Fast-track protocols in improving postoperative functional recovery and quality of life in patients with tumors of the female reproductive system. A total of 103 patients who underwent surgical treatment were included in the study and divided into two groups: 49 patients managed according to Fast-track principles and 54 patients treated using the standard approach. The Fast-track program included preoperative carbohydrate loading, respiratory exercises, thromboembolism prophylaxis, early physiotherapy, and active patient participation in the treatment process, allowing for individualized rehabilitation.
Keywords: Fast-track protocols, functional recovery, quality of life, ECOG scale, EQ-5D index, early mobilization, comprehensive rehabilitation, oncogynecological patients.